ISLAMIC CULTURAL AND EDUCATIONAL SOCIETIES, PRINTING HOUSES, NATIONAL PRESS AND MUSLIM ENLIGHTENMENT IN THE NORTHERN CAUCASUS IN THE FIRST THIRD OF THE XX CENTURY - Navruzov, Amir Ramazanovic (History, Archeology and Ethnography of the Caucasus, 2023)
The article covers some aspects of the educational activities of the reformers-enlighteners of the first third of the 20th century, who paved the road for the formation and development of Muslim enlightenment in Dagestan and the entire North Caucasus. The creation in 1903 of the M. Mavraev’s Islamic printing house in Temir-Khan-Shura marked the beginning of the mass publication of printed materials of an educational nature in Arabic and Dagestan languages using Arabic graphics. The role of the cultural and educational societies of Dagestan, created during this period at the expense of jamaats and sadaqa (donations), zakat, wills, waqfs, is enormous. The press in Arabic and national languages, which contributed to the enlightenment of the Dagestan peoples and the development of national languages and cultures, was invaluable for the promotion of Islamic educational ideas and the formation of public opinion. In the first third of the 20th century, groups of like-minded people formed in the region. They aimed to form a new perception of Islam in the Muslim environment in the industrial era during the integration of the Muslims of the North Caucasus into the Russian legal space. Among them are figures such as Ali Kayaev, Abusufyan Akaev, Muhammadmirza Mavraev, Badavi Saidov, Muhammad Dibirov, Saifulla-kadi Bashlarov, editorial boards of newspapers in Arabic and Dagestan languages: Avar, Lak, Kumyk, as well as many other Muslim reformers and enlighteners, collaborating in these publications. All this together gave a powerful impetus to the formation and development of Muslim enlightenment in Dagestan and the entire North Caucasus in the first third of the 20th century.